Answer:
A
Step-by-step explanation:
(x-4)^2=5
(x-4)(x-4)=5
x(x-4)-4(x-4)=5
distribute
x^2-4x-4x+16=5
combine like terms
x^2-8x+16=5
move terms to the left and combine
x^2-8x+11=0
use the quadratic formula and simplify
x=-(-8)+/-2 to the square roots of 5 over 2
separate and solve
x=4+ square root of 5
x=4- square root of 5
ANSWER: x=4+/- square root of 5
Answer:
Step-by-step explanation:
Well there are 500 of you going to se a regular movie
<span>All of the following are examples of composite numbers except which one?
2.</span>
Answer:
errr polynomials ahaha
so basically we can multiply the power outside of the parantheses with the exponents on the inside:
so
![-3x^{2*4} y^{1*4}](https://tex.z-dn.net/?f=-3x%5E%7B2%2A4%7D%20y%5E%7B1%2A4%7D)
this will give us:
-3x^8y^4
we also unfortunately, have to use the power on the coefficient -3 as well and we cant just MULTIPLY -3 by 4, we are going to have to multiply -3 with -3 4 TIMES(anytime we see a coefficient we MUST multiply the coefficient by itself according to the number outside of the parantheses)
so:
-3*-3*-3*-3=81
final expression
![81x^{8}y^{4}](https://tex.z-dn.net/?f=81x%5E%7B8%7Dy%5E%7B4%7D)